KEBIASAAN OLAHRAGA DENGAN KEJADIAN DISMENOREA PADA REMAJA PUTRI DI KOMUNITAS SENAM AEROBIK MOJOKERTO - Indah Kusmindarti (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2016)
ABSTRACTIntroduction: Menstruation causes pain, especially at the beginning of menstruation. This pain typically begins when menstrual blood comes out or shortly before menstrual blood comes out and reaches a peak in 24 hours. The incidence of dysmenorrhea will increase with a lack of exercise. The purpose of this study was to determine the relationship between exercise habits and the incidence of dysmenorrhea in young women. Method: The study design used correlational analytic with cross sectional approach. The population is all young women in the aerobics gymnasium Dr. Tri Widodo Basuki Jabon Mojoanyar Mojokerto. A sample of 30 adolescents were taken in total. Sources of data use primary data collected using a questionnaire. Analysis of research data using the Chi Square test. Results: most respondents had regular exercise habits, which were 18 respondents (60%) and most respondents did not experience dysmenorrhoea as many as 18 respondents (60%). Fisher exact test results with the results of 0.024 <0.05 so that H0 was rejected and H1 was accepted, which means that there is a relationship between exercise habits and the incidence of dysmenorrhea in the aerobic gymnastics community of Tri Widodo Basuki Jabon Mojoanyar Mojokerto. Conclusion: Respondents who experienced dysmenorrhea said that health status gradually became better, besides they stated the degree of pain during menstruation before and after it also appeared to have changed. If previously they felt pain that disrupted the activity then after taking exercise the menstrual pain was reduced and there were respondents who said they were completely gone.